A Nonparametric Model for Stationary Time Series. (13th August 2015) - Antoniano‐Villalobos, Isadora; Walker, Stephen G.
Abstract : Stationary processes are a natural choice as statistical models for time series data, owing to their good estimating properties. In practice, however, alternative models are often proposed that sacrifice stationarity in favour of the greater modelling flexibility required by many real‐life applications. We present a family of time‐homogeneous Markov processes with nonparametric stationary densities, which retain the desirable statistical properties for inference, while achieving substantial modelling flexibility, matching those achievable with certain non‐stationary models. A latent extension of the model enables exact inference through a trans‐dimensional Markov chain Monte Carlo method. Numerical illustrations are presented.